CHANGES OF SUCROSE CONTENT AND INVERTASE ACTIVITY DURING SUGARCANE STEM STORAGE - Siswoyo, Tri Agus; Oktavianawati, Ika; ., Djenal; Sugiharto, Bambang; Murdiyanto, Untung (Indonesian Agency for Agricultural Research and Development - MOA, 2007)
ABSTRACTInvertases (beta-D-fructofuranosidase, E.C. 3.2.1.26) are the keyenzymes involved in sucrose metabolism in sugarcane plants.They are highly correlated with sucrose and reducing sugar contentsduring plant growth. The sugarcane plants have two kindsof invertases, namely neutral invertase (NI) and acid invertase(AI). They have different function in sucrose accumulation.The research aimed to study the role of AI and NI in accumulationof reducing sugar during storage of sugarcane stems. Plantmaterials of 18-month-old field grown sugarcane of the commercialvariety R-579 (wet-land) and M 442-51 (dry-land) wereused. Three internodes were sampled to represent immature(internode 1-8/F1), maturing (internode 9-16/F2), and mature(internode 17-24/F3) stem tissues. All tissues were stored for0-9 days at room temperature (28-32oC) and each day, the samplewas extracted to determine invertase activity, total solubleprotein, and sugar contents. This observation was valid forinvertase activity expressed on a protein basis. At the initiateharvested (0-3 days), NI had a higher specific activity than AIin the sucrose-accumulating region of the sugarcane stems.Negative significant correlation was found between NI specificactivity and sucrose accumulation (r2 = 0.41, P < 0.05). AIshowed a higher specific activity after 4 days harvested and hadnegative correlation with sucrose accumulation (r2 = 0.40, P <0.05). These results showed that NI could be more responsiblein sucrose hydrolisis than AI at early storage of sugarcane stems.